Broadband HMSIW antenna using a demi hexagonal ring slot for X-band application - Astuti, Dian Widi; Muslim, Muslim; Umaisaroh, Umaisaroh; A Majid, Huda; Alam, Syah (SINERGI, 2025)
Microstrip antennas offer several advantages, including small size, easy fabrication, controllable polarity and radiation patterns, and easy integration with other components. These qualities make microstrip antennas more reliable than other antenna types. However, they also have limitations, such as lower radiation efficiency and narrow bandwidth, primarily due to the thin substrate thickness. Substrate integrated waveguide (SIW) is a type of microstrip antenna. SIW antennas come in two forms: one with a rectangular shape, typically designed as a slot, and the other in the form of a horn. However, SIW slot antennas face challenges with narrow impedance bandwidth due to the thin substrate, unlike conventional bulky hollow waveguides. The half-mode substrate integrated waveguide (HMSIW) slot antenna, which is a 50% miniaturized version of the SIW slot antenna, also suffers from reduced fractional bandwidth, resulting from the miniaturization and the thin substrate. This paper focuses on enhancing the bandwidth of HMSIW antennas by incorporating a demi-hexagonal ring slot. The broadband impedance bandwidth simulation (27.36%) is achieved through triple resonance frequencies to address the issue of narrow impedance bandwidth. Both the simulation results and measurements show consistency, with the measured impedance bandwidth ranging from 8.91 to 12.62 GHz (34.46%), demonstrating at least triple resonance frequencies.